Exploring EFL learners' perception toward the difficulties in oral presentation - Bunrosy Lan; Vireak Keo; Rany Sam; Wen Roeut (ELT Forum: Journal of English Language Teaching, 2024)
This study investigated the challenges in oral presentations, strategies to improve these skills, and the influence of lecturers in enhancing students' oral presentation abilities. The researcher employed quantitative research. Descriptive and inferential statistics were applied using SPSS to analyze data from a sample of 200 EFL students out of 400 at a university in Cambodia. The questionnaire was slightly adjusted to align with the study's objectives and context. The findings indicate that EFL students face obstacles such as insufficient time to prepare for presentations, presentation nervousness, and discomfort with peer judgment. The results of an independent sample t test revealed no significant difference between genders, t (198) = 1.062, p = 0.289, while one-way ANOVA revealed that there was a statistically significant difference in oral difficulties among the different class levels (f (3, 196) = 3.294 & p=.022). There was no statistically significant difference among the different class levels in terms of coping strategies (f (3, 196) =2.220 & p=.087), and there was a statistically significant difference among the different class levels (f (3, 196) = 4.328 & p= .006). Additionally, EFL learners employ various strategies to enhance their oral presentation skills, including observing others, building confidence, using visual aids, and relying on concise notes rather than scripted content. Educators play a crucial role in students' improvement by allowing ample preparation time, promote supportive environments, and providing constructive feedback. Understanding these specific challenges in oral presentations enables educators to effectively adjust instructional approaches with greater precision.